Avaliação de variáveis cardiovasculares e de qualidade de vida em pacientes com insuficiência cardíaca e fração de ejeção reduzida na presença e ausência de diabetes mellitus tipo 2 - Oliveira, Maria Carolina Derencio (2018)
Introduction: The changes imposed by congestive heart failure (CHF) on health status and poor prognosis can influence the behavior of autonomic cardiac modulation and worsen the quality of life (QL) of these individuals, especially in the presence of type 2 diabetes mellitus (DM2). Objectives: To evaluate whether cardiovascular variables and cardiac autonomic modulation are more affected in individuals with CHF and reduced left ventricular ejection fraction (LVEF) in the presence of DM2 when compared to isolated CHF. Methodology: Individuals diagnosed with CHF and DM2, distributed in 2 groups: GHF and GHFDM2. All were submitted to echocardiogram examination, assessment of the degree of physical activity, evaluation of QL and assessment of cardiac autonomic modulation. Statistical analysis: Student's t-test or Mann-Whitney test, Chi-square test and Fisher's exact test, with significance level of p <0.05. Results: i) GHF presented a mean RR interval response (iRR) to active postural change, however, the heart rate variability index didn’t change in response to this maneuver; ii) In the individuals studied, the DM2 associated with CHF doesn’t modify the QL. Conclusion: Individuals with isolated CHF respond to active postural maneuvers only with adjustments of the mean iRR, and that the presence of DM2 in CHF doesn’t modify the QL of these individuals.